Androgen Plays a Potential Novel Hormonal Therapeutic Role in Th17 Cells Predominant Neutrophilic Severe Asthma by Attenuating BECs Regulated Th17 Cells Differentiation via MBD2 Expression. (25th August 2022) - Wasti, Binaya; Chen, Zhifeng; Yuan, Yu; He, Yi; Duan, Wentao; Jia, Jingsi; Li, Danhong; Xiao, Bing; Li, Jianmin; Liu, Yi; Liu, Shaokun; Zhang, Dongshan; et al.
Abstract : T helper 17 (Th17) cells subtype of non-T2 asthma is less responsive (resistant) to inhaled corticosteroids (ICS), so also called severe asthma. Methyl-CpG-binding domain protein 2 (MBD2) regulates the differentiation of the Th17 cells, showing the possibility of a therapeutic target in severe asthma. Androgen tends to show beneficial therapeutic effects and is a "hot research topic, " but its role in the differentiation and expression of Th17 cells via MBD2 is still unknown. The aim of this study was to evaluate how sex hormone interacts with MBD2 and affects the differentiation and expression of Th17 cells in severe asthma. Here, first, we measured the concentration of androgen, estrogen, and androgen estrogen ratio from subjects and correlated it with severe asthma status. Then, we established an animal model and bronchial epithelial cells (BECs) model of severe asthma to evaluate the role of MBD2 in the differentiation and expression of Th17 cells (IL-17), the therapeutic potential of sex hormones in severe asthma, and the effect of sex hormones in BECs regulated Th17 cells differentiation via MBD2 at the cellular level. Increased MBD2 expression and Th17 cells differentiation were noted in the animal and the BECs severe asthma models. Th17 cell differentiation and expression were MBD2 dependent. Androgen attenuated the differentiation of BECs regulated Th17 cells via MBD2 showing BECs as a therapeutic target of androgen, and these findings postulate the novel role of androgen in Th17 cells predominant neutrophilic severe asthma therapy through targeting MBD2.